A cognitive training intervention increases resting cerebral blood flow in healthy older adults - Mozolic, Jennifer L.; Hayaska, Satoru; Laurienti, Paul J. (Frontiers in Human Neuroscience, 2010)
Healthy aging is typically accompanied by some decline in cognitive performance, as well as by alterations in brain structure and function. Here we report the results of a randomized, controlled trial designed to determine the effects of a novel cognitive training program on resting cerebral blood flow and gray matter volume in healthy older adults. Sixty-six healthy older adults participated in eight weeks of either a training program targeting attention and distractibility or an educational control program. This training program produced significantly larger increases in resting cerebral blood flow to the prefrontal cortex than the control program. Increases in blood flow were associated with reduced susceptibility to distraction after training, but not with alterations in gray matter volume. These data demonstrate that cognitive training can improve resting cerebral blood flow in healthy older adults and that cerebral perfusion rates may be a more sensitive indicator of the benefits of cognitive training than volumetric analyses.